STRATEGI PASANGAN LONG DISTANCE MARRIAGE DALAM MEMPERTAHANKAN HUBUNGAN PERNIKAHAN : STUDI FENOMENOLOGIS - Fitri, Diah Ramadani; Ema (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Long-distance marriage is a significant issue, particularly in rural areas where many residents work as Indonesian Migrant Workers (PMI), such as in Baturaden Village, Karawang Regency. This study aims to describe the communication experiences of couples in maintaining their long-distance marital relationships. The research employs a qualitative approach using Alfred Schutz’s phenomenological method. Data were collected through participant observation, in-depth interviews, and documentation involving five couples, in which one spouse, typically the wife, had worked abroad. The findings indicate that these couples face communication challenges, including time constraints, media limitations, and prolonged physical longing. However, they are able to manage conflicts through openness, mutual trust, and adaptation to communication technologies. The success in sustaining the marriage is influenced by shared commitment, the meaningfulness of family, and long-term goals such as children's education and economic improvement. This study contributes to the discourse on interpersonal and family communication within the context of labor migration.